O zagadkowej nazwie osobowej: Mazalon - Czaplicka-Jedlikowska, Maria (Słowo. Studia językoznawcze, 2021)
The article and its graphic attempts to establish the origin of the personal name Masalon [a German citizen] and a graphic version of Mazalon [a Polish citizen], which for people signing with this surname is still a mystery. The bearers of this surname look for traces of traces of the origin of the root maz- as an appellative basis for the personal name Mazalon in the dictionaries of Polish and other European languages, because they want to establish the linguistic origin of their surname and the place on the map associated with their roots. The article discusses several paths of such searches and deliberations on the recorded forms.